Clinical and reproductive outcomes of uterine smooth muscle tumor of uncertain malignant potential: a single-center retrospective study. Issue 4 (April 2021) - Ning, Chengcheng; Zhang, Lihong; Zhao, Chenyan; Chen, Xiaojun; Liu, Xiaoxia; Gu, Chao
Objective: To evaluate the clinical outcomes, histopathological features, and obstetric and oncological outcomes of uterine smooth muscle tumor of uncertain malignant potential (STUMP). Methods: We conducted a single-center, database review of patients with STUMP between January 2001 and December 2015. We investigated the clinical, operative, histopathologic, recurrence, and fertility outcomes of the included cases. Results: Nineteen patients with STUMP were studied. Three were reclassified as sarcoma after slide review, and 16 patients were finally included in the study. The mean age was 45 years. Ki-67 expression was ≥10% in 25.0% of cases and 30% in the only recurrent case. Recurrence occurred 52 months after a diagnosis of STUMP in a 56-year-old female patient who underwent hysterectomy. Two of six patients who underwent myomectomy had fertility requirements, and both successfully delivered babies without recurrence. Recurrence was not related to mitosis, degree of atypia, or necrosis. There was also no relationship between type of surgery or surgical approach and recurrence. Conclusions: Patients with STUMP warrant a pathological review process in centers with experience. Fertility-preservation is worth attempting, but young patients must be followed-up closely. Ki-67 might be a valuable marker predicting recurrence.